2020
DOI: 10.1186/s12943-020-01207-4
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between N6-methyladenosine (m6A) modification and noncoding RNAs in cancer

Abstract: As a critical internal RNA modification in higher eukaryotes, N 6-methyladenosine (m 6 A) has become the hotspot of epigenetics research in recent years. Extensive studies on messenger RNAs have revealed that m 6 A affects RNA fate and cell functions in various bioprocesses, such as RNA splicing, export, translation, and stability, some of which seem to be directly or indirectly regulated by noncoding RNAs. Intriguingly, abundant noncoding RNAs such as microRNAs, long noncoding RNAs, circular RNAs, small nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
231
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(244 citation statements)
references
References 104 publications
(219 reference statements)
2
231
0
Order By: Relevance
“…Evidence has revealed the biogenesis of circRNAs in eukaryocytes, including splicing factor, eukaryotic initiation factor, and N 6 -methyladenosine (m 6 A). 9 , 10 , 11 , 12 , 13 Abundant circRNAs are ubiquitous in eukaryotes, and circRNAs have recently been identified as a new class of regulatory RNAs with genes, including cellular development, neural differentiation, energy metabolism, and occurrence. Being benefited by the covalently closed loop, circRNAs are naturally resistant to exonuclease degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has revealed the biogenesis of circRNAs in eukaryocytes, including splicing factor, eukaryotic initiation factor, and N 6 -methyladenosine (m 6 A). 9 , 10 , 11 , 12 , 13 Abundant circRNAs are ubiquitous in eukaryotes, and circRNAs have recently been identified as a new class of regulatory RNAs with genes, including cellular development, neural differentiation, energy metabolism, and occurrence. Being benefited by the covalently closed loop, circRNAs are naturally resistant to exonuclease degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have recently shown the importance of the intricate signaling at genetic, transcriptomic, and epigenetic levels that affects tumorigenesis and progression of breast cancer [6][7][8]. N6-Methyladenosine (m 6 A) is one of the most common internal epigenetic modifications found in RNA molecules [9].…”
Section: Introductionmentioning
confidence: 99%
“…N6-Methyladenosine (m 6 A) is one of the most common internal epigenetic modifications found in RNA molecules [9]. After its discovery by Desrosiers in the 1970s [10], owing to the limitations in technology, research on m 6 A modification has slowly gained attention in the past couple of decades. Recently, with the advances in molecular biology and sequencing, the research on m 6 A modification has made remarkable progress [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The abnormal expression of m6A "writer" proteins results in abnormal levels of m6A modi cation in tumor cells, which further abnormalizes the metabolism of tumor-related genes mRNA, thereby promoting the development of a variety of cancers [8,9]. The upregulated METTL3 in gastric cancer was positively correlated with the poor prognosis of patients, and METTL3 promoted epithelial-mesenchymal transition of gastric cancer, leading to tumor invasion and metastasis [10].…”
mentioning
confidence: 99%